Empowering University Students: The Impact of a Time Management Workshop on Academic Self-Efficacy - Wang, Tian; Syafiq, Muhammad (KMAN Counseling & Psychology Nexus, 2023)
This study aimed to evaluate the effectiveness of an 8-session time management workshop designed to enhance academic self-efficacy among university students. It hypothesized that participants undergoing the workshop would demonstrate significant improvements in academic self-efficacy compared to a control group receiving no intervention. A randomized controlled trial design was employed, with 40 undergraduate students aged 18-25 years randomly assigned to either an intervention group (n=20) or a control group (n=20). The intervention group participated in an 8-session workshop, each lasting 75 minutes, covering various aspects of time management. Academic self-efficacy was measured using the Academic Self-Efficacy Scale (ASES) at baseline, immediately post-intervention, and at a four-month follow-up. Data were analyzed using SPSS-27, employing repeated measures analysis of variance (ANOVA) with Bonferroni post-hoc tests to assess changes over time and between groups. The intervention group showed a significant increase in academic self-efficacy scores from baseline to post-intervention (Mean Diff. = 9.01, p < 0.01), which was maintained at the four-month follow-up. The control group, in contrast, showed no significant changes in their scores over time. The ANOVA revealed significant time (p < 0.01, η² = 0.20), group (p < 0.01, η² = 0.25), and time × group interaction effects (p < 0.01, η² = 0.22), indicating the workshop’s effectiveness in enhancing academic self-efficacy. The time management workshop significantly enhanced academic self-efficacy among university students, with effects sustained over a four-month period. These findings suggest that structured time management interventions can be an effective strategy for improving students’ academic self-belief and potentially their academic performance. Further research with larger and more diverse samples is recommended to generalize these findings.